Sytuacje komunikacyjne a umiejętności tworzenia wypowiedzi przez młodych użytkowników języka polskiego na terenach Ukrainy Zachodniej - Zielińska, Maria (Słowo. Studia językoznawcze, 2012)
The article is devoted to the analysis of utterances created by young Polish speakers in different communication situations. All the children declare Polish descent and attend Polish Saturday (Sunday) schools in Western Ukraine. The results were obtained by means of questionnaire. The research includes such speech acts as greeting, requesting, suggesting and ordering. On the basis of the pupils” utterances conclusions about their communicative competence level can be drawn.